Accumulation of Biological and Behavioral Data of Female Sex Workers Using Respondent-Driven Sampling Around the World: Systematic Review - Bhatta, Mihir; Majumdar, Agniva; Ghosh, Piyali; Banerjee, Sitikantha; Chakraborty, Debjit; Biswas, Subrata; Sahoo, Srijan; Dutta, Shanta (Epidemiology and Society Health Review (ESHR), 2024)
Background: Respondent-Driven Sampling (RDS) is generally used to study hidden or hard-to-reach populations. The objective of the present work is to describe the initiation, implementation, and complications that arise during RDS of female sex workers (FSWs) around the world. Method: Behavioural and biological data of FSWs collected through RDS was mined from peer-reviewed articles, published during 2010-2022. Review protocol was developed and registered in the PROSPERO (registration number CRD42022346470) and published separately. Results: It was found that most of the RDS (69 articles, globally) were largely successful in the recruitment of FSWs, with varying response rates. Conclusion: Present outcomes supports the application of RDS in surveillance for any such population by providing a minimal set of parameters of testing procedures (methodology) including methods to evaluate the quality also.